2018
DOI: 10.1177/016146811812001402
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Racist Change: A Conceptual Framework for Educational Institutions to Take Systemic Action

Abstract: To achieve racial equity in education not only do individuals’ mindsets need to be shifted to a more anti-racist ideology, but the institutions in which they work need to make profound anti-racist changes as well. Therefore, we revisit two sets of literature, research on anti-racism and organizational change, to explore what actions and leadership attributes could foster actual institutional change for racial equity. However, we do acknowledge the limitations of each body of research. Anti-racism research is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 45 publications
3
93
0
Order By: Relevance
“…Diversity frameworks, which are broadly conceptualized to address diversity, inclusion, and marginalization, can sometimes “soften” or dilute the critical need to address racial equity within higher education 65 . The generalized concepts of diversity or inclusion are usually more comfortable or less intimidating than conversations about race and racism.…”
Section: An Antiracism Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversity frameworks, which are broadly conceptualized to address diversity, inclusion, and marginalization, can sometimes “soften” or dilute the critical need to address racial equity within higher education 65 . The generalized concepts of diversity or inclusion are usually more comfortable or less intimidating than conversations about race and racism.…”
Section: An Antiracism Frameworkmentioning
confidence: 99%
“…Diversity frameworks, which are broadly conceptualized to address diversity, inclusion, and marginalization, can sometimes "soften" or dilute the critical need to address racial equity within higher education. 65 The generalized concepts of diversity or inclusion are usually more comfortable or less intimidating than conversations about race and racism. However, recent events tied to COVID-19, increased discrimination against Asian Americans, and the deaths of George Floyd and Breonna Taylor have made it clear that issues of access and equity in health care, the criminal justice system, employment, and education, can only be truly addressed by dissecting the historical foundations of race and its role within the U.S.…”
Section: An Antiracism Frameworkmentioning
confidence: 99%
“…In such contexts, leaders' utilization of routines is described as a critical tool to navigating tensions between accountability forces and autonomy in leading changes (Datnow et al, 2020;Hubers et al, 2017). Moreover, research on equity leadership informed by organizational improvement has shown that leaders can promote equity, social justice and democracy through organizational routines-formal roles, division of labor, professional development, meetings-as part of the organizational improvement (Dowd and Liera, 2018;Irby, 2018;Welton et al, 2018), although the existing routines can also hinder realizing changes that leaders intended. These findings imply that school leaders may often face both positive and negative feelings toward bureaucracy in schools.…”
Section: Ambivalent Responses To Bureaucracymentioning
confidence: 99%
“…, 2017). Moreover, research on equity leadership informed by organizational improvement has shown that leaders can promote equity, social justice and democracy through organizational routines—formal roles, division of labor, professional development, meetings—as part of the organizational improvement (Dowd and Liera, 2018; Irby, 2018; Welton et al. , 2018), although the existing routines can also hinder realizing changes that leaders intended.…”
Section: Introductionmentioning
confidence: 99%
“…Even in K-12 schooling, the research is limited with two special issues planned on pro-Black pedagogy for the Journal of Early Childhood Literacy for the same publication date as this special issue (see https://journals.sagepub.com/doi/10.1177/14687984211049530). When the literature does consider post-secondary institutions, the studies tend to focus on institutional change, addressing the role of leaders, Black faculty experiences or White students’ responses to content focused on racism (Welton, et al , 2018; Ruemper, 1996; Law, 2017; Ash et al , 2020). This knowledge is important for changing the racist systems embedded within these institutions, but does not discuss the need for spaces that are developed to welcome and empower Black students and actively address their needs nor the pedagogical practices that achieve these ends.…”
Section: Anti-racism and Pro-black Educational Practicementioning
confidence: 99%